Assembling geographies of diplomacy under neoliberalism. Issue 1 (20th August 2017) - Jones, Alun; Clark, Julian
Abstract : There is an enormous gap in our understanding of the state's role in the construction of international markets. Specifically, diplomacy's position in the contemporary entanglement of state and markets has been overlooked. Increasingly, diplomacy's on‐going adaptation to support neoliberalism has led to diplomats operating in a "twilight world" between diplomacy and business. Using assemblage thinking, we investigate the codings, capacities and tendencies emerging in the social spaces of diplomatic possibility in this "twilight world". Drawing on comprehensive empirical materials on the UK–India diplomatic relationship, we show how the material and expressive components of the UK Foreign Office assemblage are being deployed to champion state goals in global markets. We illustrate the ways in which diplomacy struggles in the name of the state's international competitiveness. In particular, we argue that these social spaces of possibility are structured by both diplomatic and business calculations that have the capacity to create new and unpredictable courses that render both an uncertainty and fuzziness to the agential interactions between assemblages.